Identification and characterization of membrane receptor protein YueB in Bacillus subtilis isolated from Thua Nao (Thai fermented soybean) - Pornthip Chawapun (2020)
© 2019, Khon Kaen University,Research and Technology Transfer Affairs Division. All rights reserved. Thua nao (Thai fermented soybean) is a conventional and spontaneously fermented soybean in northern Thailand. The fermentation process relies on certain microbial activities, especially the Bacillus species. Bacteriophage contamination on Thua nao can rapidly decrease the Bacillus growth and the quality of any related products. The bacteriophage infection occurred through the YueB membrane receptor protein (coded by yueB gene) on the bacterial surface. Twenty isolates including Bacillus spp. were isolated from Thua nao. Phylogenetic analysis of Bacillus was determined using 16S-23S rRNAs nucleotide sequencing and compared with those obtained from the GenBank® database. Twenty Bacillus spp. isolated were classified into six clusters, which included Bacillus amyloliquefaciens, B. aryabhattai, B. cereus, B. licheniformis, B. sonorensis, B. subtilis and B. vallismortis. B. subtilis isolate TM4, TM5, TK7 and MR4 were selected to determine the variation of nucleotide sequences of yueB gene. Approximately 3.2 kb of yueB gene were amplified by Polymerase chain reaction (PCR) and directly sequencing. The translation of proteins retrieved 1,059 amino acid residues in all the isolate strains. The similarity alignment protein sequence of B. subtilis 168 as a reference strain revealed maximum identity scores of 81% and 1% of the gaps on the protein BLASTX alignment tools. The secondary structure of YueB protein indicated that the six transmembrane domain regions at one N-terminal and five C-terminal from B. subtilis isolate MR4, TK7, TM4 and TM5 were similar to that of B. subtilis 168. At the position between 200 to 600 amino acid residues, four regions were folded as coiled coil structures.